Sap Flow Velocity in Fraxinus pennsylvanica in Response to Water Stress and Microclimatic Variables - Su, Yu; Wang, Xinyu; Sun, Yiqiu; Wu, Hailong (Frontiers in Plant Science, 2022)
In arid and semiarid regions with water shortage, forestry development is limited by water availability. Understanding how tree sap flow responds to water stress and microclimatic variables is essential for the management of trees and the understanding of the eco-physiological properties of trees in arid areas. In the city of Tianjin in northern China, we measured the sap flow of Fraxinus pennsylvanica, a widely distributed urban greening tree species in semiarid regions of China. We measured the sap flow in four F. pennsylvanica trees over six months (April–September 2021), using a thermal diffusion probe method, and simultaneously monitored microclimatic variables and soil moisture. Results indicated that high nighttime sap flow velocity might be produced under the water stress condition. In addition, the nighttime sap flow velocity under the water stress condition was more susceptible to the combined effects of meteorological factors at night. The daytime sap flow velocity exerted a highly significant positive effect on the nighttime sap flow velocity during the whole research period, and the model fit was higher in the early growing season than that in the late growing season (early growing season: R2 = 0.51, P < 0.01; late growing season: R2 = 0.36, P < 0.01). Vapor pressure deficit had a positive effect on daytime sap flow. However, net vapor pressure deficit restrained daytime sap flow velocity when the intercorrelation between the microclimatic variables was removed. Our study highlights that drought areas perhaps have higher nighttime sap flow and that more emphasis should be placed on nighttime sap flow and the response of nighttime sap flow to microclimatic variables. In addition, the influence of other microclimatic variables on vapor pressure deficit needs to be considered when analyzing the relationship between daytime sap flow and vapor pressure deficit. An increase in net VPD can suppress the daytime sap flow.